Quantifying the sources of increasing stratospheric water vapour concentrations - P. E. Sheese; K. A. Walker; C. D. Boone; D. A. Plummer (Atmospheric Chemistry and Physics)
According to satellite measurements from multiple instruments, water vapour (H2O) concentrations, in most regions of the stratosphere, have been increasing at a statistically significant rate of ∼1 %–5 % per decade since the early 2000s. Previous studies have estimated stratospheric H2O trends, but none have simultaneously quantified the contributions from all main sources (temperature variations in the tropical tropopause region, changes in the Brewer–Dobson circulation, and changes in methane (CH4) concentrations and oxidation) at all latitudes. Atmospheric Chemistry Experiment–Fourier Transform Spectrometer (ACE-FTS) measurements are used to estimate altitude-/latitude-dependent stratospheric H2O trends from 2004–2021 due to these sources. Results indicate that rising temperatures in the tropical tropopause region play a significant role in the increases, accounting for ∼1 %–4 % per decade in the tropical lower mid-stratosphere and in the mid-latitudes below ∼20 km. By regressing to ACE-FTS N2O concentrations, it is found that, in the lower mid-stratosphere, general circulation changes have led to both significant H2O increases and significant H2O decreases on the order of 1 %–2 % per decade depending on the altitude/latitude region. Making use of measured and modelled CH4 concentrations, the increase in H2O due to CH4 oxidation is calculated to be ∼1 %–2 % per decade above ∼30 km in the Northern Hemisphere and throughout the stratosphere in the Southern Hemisphere. After accounting for these sources, there are still regions of the mid-latitude lower mid-stratosphere that exhibit significant residual H2O trends increasing at 1 %–2 % per decade. Results indicate that these unaccounted-for increases could potentially be explained by increases in upper-tropospheric molecular hydrogen.